Renovation and modernization of hotel buildings - case studies in Silesia = Renowacja i modernizacja budynków hotelowych na przykładzie projektów i realizacji na Śląsku - Bradecki, Tomasz; Uherek-Bradecka, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The cultural heritage of Silesia has different backgrounds and is often characterized by difficult to assess values. There is doubt as to whether some of the existing buildings should be modernized. Since 2000, an increase in the amount of investments in hotel buildings and conference venues in Poland has been observed. The functions and roles of hotels within a city have also changed. The paper presents examples of original projects and realizations of hotel buildings in Silesia. A discussion was also held regarding the issue of adapting and modernizing hotel buildings.
Keywords: dziedzictwo kulturowe; Śląsk; budynki hotelowe; renowacja hoteli; cultural heritage; Silesia; hotel building; hotel conservation; hotel modernization